THE CRUCIAL ROLE OF MEDICAL LABORATORIES IN IMPLEMENTING PREVENTIVE HEALTH MEASURES: AN ANALYTICAL PERSPECTIVE - Dafer Modwah Mofarh AL khorssan, Mansour Ali Gassem Al sari, Mubarak Mohammed Saad Alqufayli, Hussein Rakan Al Sherif, Ali Saleh Mohammed Al Garea, Mohammed Abdullah Ali Al Sulayym (Chelonian Research Foundation, 2023)
This article delves into the pivotal role of medical laboratories in the realm of preventive health measures, offering an analytical perspective on their contribution to public health. With the evolution of healthcare from a treatment-centric to a prevention-oriented approach, medical laboratories have emerged as fundamental pillars in detecting, monitoring, and preventing diseases. This review explores the historical context, technological advancements, and the shift towards preventive care that have underscored the importance of laboratories in the healthcare ecosystem. It critically examines the challenges faced by medical laboratories, including resource constraints, the need for standardization, and data privacy issues, while proposing viable solutions to enhance their effectiveness in preventive health. Through a series of case studies, the article highlights successful interventions and innovations in laboratory practices that have significantly contributed to public health and outlines the lessons learned from past failures. Looking forward, it discusses the potential impacts of emerging technologies like artificial intelligence and machine learning on laboratory practices and the importance of supportive policies for future advancements. The article concludes by emphasizing the indispensable role of medical laboratories in advancing public health through effective prevention strategies and calls for sustained investment and innovation in this vital sector. Keywords: Medical Laboratories, Preventive Health Measures, Public Health, Technological Advancements, Disease Surveillance, Chronic Disease Management, Laboratory Standardization, Data Privacy, Emerging Technologies, Healthcare Policy